ANALISIS FAKTOR-FAKTOR PENENTU KEBERHASILAN KLASTER (STUDI PADA KLASTER PERTANIAN TERPADU KABUPATEN SUKOHARJO) - Raden Kunto Adi; Mohamad Harisudin; Minar Ferichani (Caraka Tani: Journal of Sustainable Agriculture, 2015)
Center for Integrated Farming in Agribusiness Regency Sukoharjo is one of centers in the Sukoharjo Regency potential number of units SME’s agribusiness, which has considerable potential to further developed forward. The research method is implemented with the survey and FGD (Focus Group Discussion). The results showed stakeholders performance within Integrated Agricultural Cluster development seen from the achievement of the results of the institutional activities that had been undertaken by related agencies involved in the Integrated Agriculture cluster development in Sukoharjo, Sukoharjo Regency FEDEP, among others, the Bappeda Sukoharjo Regency, local Government of Sukoharjo through service related, and Agricultural Cluster Integrated Rembug Forum as targets of mentoring activities during this FEDEP is enough well, though still not optimal. The role of BDS (Business Development Service) as escort agency nor an escort FEDEP Integrated Agricultural Cluster during this already plays well. The role of the College during this already good. While the role of financing institution has also been good, especially Banking as long as it's been good in support of cluster development in integrated agricultural. The role of the association profession and non government (NGO) in Sukoharjo Regency have already good much seen in Integrated Agriculture cluster development Sukoharjo Regency . Determinants of the success of the integrated Agriculture Cluster, among others, specialization, research and development capacity, knowledge and skills, human resource development, networking and social capital, proximity to suppliers, capital availability, the soul of entrepreneurship, as well as leadership and shared vision. Determinants of the success of the integrated Agriculture Cluster, among others, specialization, research and development capacity, knowledge and skills, human resource development, networking and social capital, proximity to suppliers, capital availability, the soul of entrepreneurship, as well as leadership and shared vision. Some of the determinants of the success of the cluster has been running quite well for example in terms of networking and social capital, proximity to suppliers, and the spirit of entrepreneurship, while other factors are still not running optimally. Suggestions in this study include 1). Capacity building of institutional FEDEP and Agricultural Integrated Cluster Forum Sukoharjo Regency, 2) upgrade human resource in Cluster of integrated Farming, with a wide range of training courses is gradually and continuously, intensively involved with the College and the state-owned enterprises as well as private owned companies, and 3). Network Development efforts on Integrated Agricultural Cluster through the integrated system between the sub cluster, through cooperation between the sub cluster associated with the provision of raw materials, production technology, product innovation, product quality standards (certification), institutional, and product marketing, with facilitation and mentoring of stakeholders associated within FEDEP Sukoharjo Regency. The expected synergies also intercity in SOLO RAYA.